Regulation of CNS precursor function by neuronal chemokines. (10th January 2020) - Watson, Adrianne Eve Scovil; Goodkey, Kara; Footz, Tim; Voronova, Anastassia
Highlights: Neurons communicate with NPCs and OPCs via paracrine signalling and/or neuronal activity/synapses; NPCs and OPCs express chemokine receptors and respond to chemokines; Neuronally secreted chemokines regulate NPC and OPC migration, survival, proliferation and differentiation; Variants in genes encoding chemokine ligands and receptors are detected in patients with MS and neurodevelopmental disorders; Aberrant neuron-precursor chemokine signalling may play a role in the development of these disorders. Abstract: Oligodendrocyte and neural precursor cells (OPCs and NPCs, respectively) in the central nervous system (CNS) have diverse roles in development and homeostasis. During development, precursors build the CNS. In adulthood, they maintain their ability to proliferate and generate differentiated progeny, indicating their tremendous potential to regenerate and repair injured or degenerated CNS. How can we utilize this capability? Cross-talk between neurons and OPCs may hold some clues. Neurons communicate with OPCs via two mechanisms: 1) paracrine secretion of ligands, and 2) neuronal activity and bona fide synapses with OPCs. Intriguingly, OPCs express receptors for chemokines, which are small signalling molecules produced by various cells, including neurons. In addition to inducing chemotaxis, chemokines also regulate cell proliferation, survival and differentiation. In this review, we will summarize the roles of neuronally secreted chemokines and their documented ability to directly regulate the diverse functions of OPCs and NPCs in the developing as well as adult normal and injured CNS. We will focus on the following neuronal chemokines: CCL2, CCL3, CCL20, CCL21, CXCL1, CXCL8, CXCL9, CXCL10, CXCL11, CXCL12 and CX3CL1. We will discuss the implications for neuronal chemokine signalling in OPCs and NPCs not only in developmental myelination and adult CNS regeneration, but also in cognition, behavior, neuroinflammation and neuronal function.